Advances in fig research and sustainable production - Flaishman, Moshe A.; Aksoy, U. (Uygun) (CABI, 2022)
"This book provides a comprehensive review of fig research, both basics and applications. It addresses the recent scientific results in genetics, genomics, metabolomics, pharmaceutical properties, understanding of symbiosis, new management, post-harvest technology and diseases and pest management of figs"--